Design and preparation of a novel fluorescent naphthalimide derivative supramolecular self-assembly system and its bioimaging application. Issue 9 (2nd September 2019) - Li, Yiran; Li, Qiongya; Gao, Aiping; Wu, Jie; Wu, Yongquan; Cao, Xinhua
ABSTRACT: A novel fluorescent naphthalimide derivative gelator (N-18 ) was designed and characterised which could form a stable gel in 1, 4-dioxane/H2 O (2/1, v/v), methyl sulfoxide (DMSO), ethanol/H2 O (4/1, v/v), acetone/H2 O (2/1, v/v) and methanol. The self-assembly process of moleculeN-18 in the five solvents was carefully investigated by the field emission scanning electron microscope, UV-vis absorption spectra, fluorescence emission spectra, fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD) and water contact angle experiments. Different structures from microbelts to helical nanofibers were formed in the self-assembly process. Hydrogen bonding and π–π stacking interaction were the mainly driving forces for the formation of gel. At the same time, the hydrophobic surface with the contact angles of 133°–142° was observed on the xerogel filmsN-18 from the above five solvents. Interestingly, moleculeN-18 could be applied in bioimaging in a living cell. GRAPHICAL ABSTRACT: